Management: A Real World Approach - Ghillyer Andrew (Mc Graw Hill, 2008)
Many principles of management textbooks make the assumption that students already have a stable understanding of the subject. Management: A Real World Approach, combines the theory students need with examples within their grasp as well as providing reinforcing exercises and activities to help them retain and apply what they have learned. This text along with the ancillary materials help address the question that many students ask when taking a principles of management course: “What does management mean to me?”